Synergistic anti-tumor effect of 17AAG with the PI3K/mTOR inhibitor NVP-BEZ235 on human melanoma. (10th October 2017) - Calero, R.; Morchon, E.; Martinez-Argudo, I.; Serrano, R.
Abstract: Drug resistance by MAPK signaling recovery or activation of alternative signaling pathways, such as PI3K/AKT/mTOR, is an important factor that limits the long-term efficacy of targeted therapies in melanoma patients. In the present study, we investigated the phospho-proteomic profile of RTKs and its correlation with downstream signaling pathways in human melanoma. We found that tyrosine kinase receptors expression correlated with the expression of pivotal downstream components of the RAS/RAF/MAPK and PI3K/AKT/mTOR pathways in melanoma cell lines and tumors. We also found high expression of HSP90 and the PI3K/AKT/mTOR pathway proteins, 4EBP1 and AKT compared with healthy tissue and this correlated with poor overall survival of melanoma patients. The combination of the HSP90 inhibitor 17AAG with the PI3K/mTOR inhibitor NVP-BEZ235 showed a synergistic activity decreasing melanoma cell growth, inducing apoptosis and targeting simultaneously the MAPK and PI3K/AKT/mTOR pathways. These results demonstrate that the combination of HSP90 and PI3K/mTOR inhibitors could be an effective therapeutic strategy that target the main survival pathways in melanoma and must be considered to overcome resistance to BRAF inhibitors in melanoma patients. Highlights: Several tyrosine kinase receptors are upregulated in melanoma. RTKs expression correlates with RAS/RAF/MAPK and PI3K/AKT/mTOR pathways expression in melanoma cell lines and tumors. HSP90 and PI3K/AKT/mTOR components overexpression and correlation with poor overall survival of melanoma patients. 17AAG and NVP-BEZ235 has a synergistic effect on melanoma cells.